2008
DOI: 10.1071/ea08134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antioxidant properties of emu oil with other avian oils

Abstract: The antioxidant properties of emu oil were compared with oils derived from the fat of other avian species. We first examined their free radical scavenging activity against the 2,2-diphenyl-1-picryl hydracyl radical. The concentration of emu oil in the test solution that caused 50% neutralisation (IC50) was variable (24.5 ± 5.9 mg/mL, range 5.3–55.4 mg/mL), but similar to values obtained for other ratites (10.7 ± 5.9 mg/mL). In contrast, the IC50 values for duck and chicken oil were much higher (118.0 ± 8.1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 26 publications
5
23
0
Order By: Relevance
“…This was further supported by a study in which Fish Oil in combination with Indomethacin decreased the severity of liver steatosis in a mouse model of familial hypercholesterolemia [38]. Based upon the n-3 PUFAs present in Emu Oil and its reported antioxidant activity [47], liver steatosis seems less likely in the current study. However, a high n-6/n-3 PUFA ratio has been implicated in nonalcoholic FA liver disease [48] and therefore it would be beneficial to determine the effects of FA ratio and n-9 FA levels on liver function in future studies.…”
Section: Discussionsupporting
confidence: 77%
“…This was further supported by a study in which Fish Oil in combination with Indomethacin decreased the severity of liver steatosis in a mouse model of familial hypercholesterolemia [38]. Based upon the n-3 PUFAs present in Emu Oil and its reported antioxidant activity [47], liver steatosis seems less likely in the current study. However, a high n-6/n-3 PUFA ratio has been implicated in nonalcoholic FA liver disease [48] and therefore it would be beneficial to determine the effects of FA ratio and n-9 FA levels on liver function in future studies.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, the increased level of MDA was restored upon treatment with emu oil. Similar findings were reported by Bennett et al [30].…”
Section: Resultssupporting
confidence: 92%
“…Emu oils have been claimed to have anti-inflammatory properties (Snowden & Whitehouse, 1997;Yoganathan et al, 2003), which are associated with causing a decrease in the production of proinflammatory cytokines (Whitehouse & Butters, 2003). It has also been reported that emu oil possesses the antioxidant and radical scavenging properties (Bennett, Code, Godin, & Cheng, 2008). Ostrich oils, in addition to being exported as such benefits of emu oils, are also currently used in cosmetic formulations and food chemistry.…”
Section: Introductionmentioning
confidence: 99%